Knowledge, Attitude, and Practice of Breast Self-Examination (BSE) Among Women in Ulu Kinta, Perak - Abdullah Zawawi, Muhamad Fahim Bin; Shafee, Muhamad Hasri Bin; Muazhar, Nur Azmina Binti; Govindan, Subhashini Nair (International Journal of Human and Health Sciences (IJHHS), 2025)
Objectives: Breast Self-Examination (BSE) is a critical early detection tool for breast cancer. This study aimed to assess the knowledge, attitudes, and practices of BSE among women in Ulu Kinta, Perak, to identify gaps and improve breast cancer prevention strategies. Methods: A cross-sectional study was conducted involving 408 women from the Ulu Kinta area, aged 15 and above. A structured questionnaire, adapted from validated sources, was administered to assess the participants’ knowledge, attitudes, and practices regarding BSE. The data were analyzed using SPSS v26 for descriptive and inferential statistics, exploring associations between socio-demographic factors and BSE-related knowledge, attitudes, and practices. Results: The findings revealed that 52% of women possessed adequate knowledge of BSE, but only 42% practised it regularly. Attitudes toward BSE were generally positive, with 60% recognizing its importance. However, socio-demographic factors, such as education level and age, showed a significant correlation with BSE knowledge and practice (p < 0.05). Women with higher education levels exhibited better knowledge and more frequent BSE practice. Conclusion: Despite reasonable awareness, the practice of BSE remains insufficient among the women of Ulu Kinta. Targeted educational interventions, focusing on both improving knowledge and promoting regular BSE practice, are crucial in enhancing early breast cancer detection rates. International Journal of Human and Health Sciences Supplementary Issue 01: 2025 Page: S28